WRITING, APPROACHES, AND GENRES - Ningrum Wijati; Fitriani Siregar; Nur Widya Ningsih (EXCELLENCE: Journal of English and English Education, 2023)
This article describes a brief description about writing, approach, genre, and writing genre. There are many classification of writing genres. The big genre category falls into fictional genre and non-fictional genre. There are more specific categories of writing genre as taken from many resources. It is expected that the readers of this article will be able to grasp understanding about writing and its genre in order to become a good reader or writer.